Analysis Quantitative Perception Students and Teachers towards Availability and Condition of Physical Education Facilities and Infrastructure in SMK Bojonegoro (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze perception students and teachers towards availability and conditions means infrastructure education physical education , sports and health (PE) in five schools Intermediate State Vocational Schools (SMK) in the District Bojonegoro , Regency Bojonegoro , Indonesia. Approach quantitative used by spreading questionnaire to 428 students and 11 PE teachers. The results of the study show variation significant in level satisfaction . As many as 31% of students feel satisfied or very satisfied satisfied , but the other 33% feel not enough satisfied or very satisfied No satisfied , especially Because cleanliness room poor replacement ( mean score 2.97 ) and limitations tool sports ( average score 3.50). On the other hand , the teacher showed satisfaction more high , with 54% feeling satisfied or very satisfied satisfied , especially in the aspect scheduling field ( average score 4.01). The gap This perception indicates the need improvements in maintenance and management facilities to support effective PE learning